Study on Barriers and Challenges Ahead in Public Private Partnership Projects - S, Sudhan; T, Pradeep; T S, Mukesh (International Journal of Scientific Research in Civil Engineering, 2016)
The Public-Private Partnership mostly did the world economic development and growth across the country. Number of schemes are started in joint collaboration with private sectors in order to give national economy an impulse and thus enhancing the pace of economic growth by the Government. PPPs aim is to combine the skills, expertise and experience of both the public and private sectors to deliver higher standard of services to the nation. In PPP, some challenges like transparency, time concern objects, lack of Latest technology and machinery, project costing, choice of best private firms and institutions, strategy formulation, capital management, absence of skilled man power etc. The purpose of this paper is to find out the various challenges and issues through some case studies that create difficulties to promote PPP.